Antibacterial Activity of Small Molecules Which Eradicate Methicillin-Resistant Staphylococcus aureus Persisters - Hamad, Mohamad; Al-Marzooq, Farah; Srinivasulu, Vunnam; Omar, Hany A.; Sulaiman, Ashna; Zaher, Dana M.; Orive, Gorka; Al-Tel, Taleb H. (Frontiers in Microbiology, 2022)
The serious challenge posed by multidrug-resistant bacterial infections with concomitant treatment failure and high mortality rates presents an urgent threat to the global health. We herein report the discovery of a new class of potent antimicrobial compounds that are highly effective against Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). The compounds were efficiently synthesized in one-pot employing a cascade of Groebke–Blackburn–Bienaymé and aza-Michael addition reactions. Phenotypic screening of the pilot library against various bacterial species including methicillin-sensitive as well as methicillin-resistant Staphylococcus aureus strains, has identified potent chemotypes with minimal inhibitory concentrations (MIC) of 3.125 to 6.25 µg/ml. The most potent compounds were fast-acting at eradicating exponentially growing MRSA, with killing achieved after 30 minutes of exposure to the compounds. They were also able to kill MRSA persister cells which are tolerant to most available medications. Microscopic analysis using fluorescence microscope and atomic force microscope indicate that these compounds lead to disruption of bacterial cell envelopes. Most notably, bacterial resistance toward these compounds was not observed after 20 serial passages in stark contrast to the significant resistance developed rapidly upon exposure to a clinically relevant antibiotic. Furthermore, the compounds did not induce significant hemolysis to human red blood cells. In vivo safety studies revealed a high safety profile of these motifs. These small molecules hold a promise for further studies and development as new antibacterial agents against MRSA infections.